PROSES MORFOLOGIS KATA BENDA DALAM BAHASA INGGRIS DAN BAHASA GORONTALO (SUATU ANALISIS KONTRASTIF) - Dama, Siskawati (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled ‘Morphological Process of Nouns in English and Gorontalo Language: a Contrastive Analysis. The objective of the analysis are to identify, and describe the morphological process of nouns in English and Gorontalo language and finding out the similarities and the differences of morphological process of nouns in English and Gorontalo language by using of O’Grady’s (1992) theory and contrastive method using Lado (1957) and Whitman (1970). The English data were collected from several English textbooks. Some of them are Morphology: Word Structure in Generative Grammar (1990) by John T. Jensen, and the data of Gorontalo Language from the native speaker’s four informants who can speak Gorontalo Language at the age of 20-60 years old in Manado. The result of this research shows that in morphological process of nouns in English and Gorontalo language have some similarities and differences. The similarities are that English and Gorontalo language have affixation as prefix and suffix, reduplication as full of reduplication, compounding as endocentries and excocentries compounding. The difference is that English language has not infix affixation but in Gorontalo language has an infix affixation, reduplication in English has full reduplication with variety of phoneme and in Gorontalo languages have a partial reduplication. Keywords: Morphological Process of Nouns, English and Gorontalo Languages, Contrastive Analysis.